A systematic review of motor control tests in low back pain based on reliability and validity. (January 2022) - Schulz, Jane; Vitt, Esther; Niemier, Kay
Abstract: Background: Low back pain (LBP) is common. Motor-control-dysfunctions (MCD) might play an important role in the development of LBP. Objectives: Find reliable and valid clinical tests to identify MCD in patients with LBP. Data sources: PubMed and Medline Library databases were searched over a period of ten years till November 2019. Data extraction: Studies examining clinical tests for MCD published in English or German were included. Studies examining clinical outcome, apparatus-based tests or acute pain were excluded. The inclusion/exclusion was determined by stated criteria and consensus between two reviewers. The risk of bias was examined by the critical appraisal tool (Brink and Louw, 2012 ). Methods: The studies were assessed according to aim, population and methods and by implementing criteria from literature (Landies and Koch, 1977 ; Portney and Watkins, 2015 ). Results: Nine studies (376 patients, 23 tests) met the inclusion criteria. 22 tests examined interrater reliability, five measured intra-rater-reliability, and five assessed the construct/discriminative validity. Fifteen tests showed good/very good interrater-reliability. The intra-rater-reliability ranged from moderate to good. Two studies evaluated construct validity with good results, and one discriminative validity with poor results. Conclusions: Tests with good reliability should be considered for validity testing Discussion: Of all the tests reviewed, two can be recommended for clinical use. All the other tests should undergo further evaluation or be reconsidered. Limitations: Relevant studies might be missed, since they were older than ten years, not included in the searched databases, be published in other languages, or were not picked up by the set criteria.